Air Quality Management On Coal Loading-Unloading Activities: a Study in Coal Port at South Sumatera - Ahmad Daudsyah Imami; Nadia Syakhira (Sustainable Environmental and Optimizing Industry Journal, 2022)
The increasing demand for coal energy globally has led to the rapid growth of the coal industry in Indonesia. It is projected that coal energy will still dominate in the world until 2050. This development will undoubtedly impact the quality of the environment, one of which is related to air pollution. As one of the distribution chain links, coal port facilities require attention regarding air quality management. This research shows that the source of fugitive pollutants from coal loading and unloading activities at the research location comes from supporting equipment for loading and unloading activities and coal stockpiles. These tools continuously emit non-chimney contaminants, namely coal dust. Non-fugitive pollution is generated by heavy equipment and generators used in activities in the workshop area. Measurement of ambient air quality at the study site indicated that the particulate parameters (TSP, PM10, and Dustfall) needed to be comparable with the standards. In contrast, the gas parameter that was the most significant was the SO2 pollutant. Efforts to control air pollution are using sprinklers and installing windproof nets, which are indicated to be quite effective in reducing dust in the crusher area. Recommendations in controlling air pollution are to automate the sprinkler system for watering and monitoring airflow and plant trees with the ability to absorb SO2 effectively.